Proactive Companies How to Anticipate Market Changes - Araújo, L. (Fundacao Dom Cabral (FDC), 2012)
Why do some companies succeed better than others? It is well known that there are many variables such which may impact a company's performance. The authors present their new model for Market Proactiveness which shows organizations how to anticipate change and respond to it before they are forced to do so, and improve their overall performance.